Society and Publishing: Book Mediation in the First Decades of the 21st Century - Velgić, Zoran (Anafora, 2023)
This paper aims to analyse the relationship between contemporary society and the publishing industry that provides a framework of possibilities of book content mediation. Four aspects are considered: the plenitude of books; censorship imposed by society or associations onto these books; the role of IT companies that started a revolution in content distribution but at the same time jeopardised intellectual property rights and, finally; the position of the publisher as the remaining sole patron of content quality. The paper is based on the content analysis of recent academic research in publishing studies as well as insights into contemporary statistics and media reports. The paper contributes to book and media research by exploring censorship imposed by certain social groups based on modern research into reading habits, observations of the positive and negative impacts of IT companies on the publishing industry and the status of authors and intellectual property and, lastly, emphasizing the role of publishers as content managers, since without them the creativity of authors remains non-public, literally invisible.